2020
DOI: 10.1371/journal.pgen.1008977
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of functional SNPs interrupting 3’UTR polyadenylation signals

Abstract: Alternative polyadenylation (APA) is emerging as a widespread regulatory layer since the majority of human protein-coding genes contain several polyadenylation (p(A)) sites in their 3'UTRs. By generating isoforms with different 3'UTR length, APA potentially affects mRNA stability, translation efficiency, nuclear export, and cellular localization. Polyadenylation sites are regulated by adjacent RNA cis-regulatory elements, the principals among them are the polyadenylation signal (PAS) AAUAAA and its main varian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…These cis-acting motifs all have in common with the MREs interacting with miRISC that they affect the stability of mRNAs in certain tissues and/or developmental stages [88][89][90]. There were also 18 over-represented motifs that had the PAS-motif (AATAAA) [11,91]. The PAS-motif function is to initiate poly-adenylation from a certain position in the 3 UTR of the precursor mRNA.…”
Section: Discovery Of Novel Putative Functional Cis-motifs By Their Over-representation In the 3 Utromementioning
confidence: 99%
See 1 more Smart Citation
“…These cis-acting motifs all have in common with the MREs interacting with miRISC that they affect the stability of mRNAs in certain tissues and/or developmental stages [88][89][90]. There were also 18 over-represented motifs that had the PAS-motif (AATAAA) [11,91]. The PAS-motif function is to initiate poly-adenylation from a certain position in the 3 UTR of the precursor mRNA.…”
Section: Discovery Of Novel Putative Functional Cis-motifs By Their Over-representation In the 3 Utromementioning
confidence: 99%
“…MicroSalmon may be used as a starting point to retrieve cis-acting motifs (both MREs and others) in FL-transcripts of interest, which can be validated by experimental methods. Furthermore, it may serve as a reference for targeted HTS studies to identify genetic variation that affect the function of such elements [91,101,107,108]. MicroSalmon also represents a resource for the discovery of transcript variants that are differently regulated due to alternative polyadenylation of the 3 UTRs.…”
Section: The Microsalmon Repistorymentioning
confidence: 99%
“…Mutations changing the PAS strength have been reported in a growing number of human diseases, including thalassemia and systemic lupus erythematosus ( 10 , 11 ). Moreover, recent studies have found that single nucleotide polymorphisms (SNPs) near the PAS can lead to changes in PAS usage and gene expression ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Variants in the 3′UTR may affect mRNA stability, translation efficiency, nuclear export and cellular location [ 31 ]. This variant does not seem to affect the polyadenylation signal region, one of the most sensitive places in the 3′UTR [ 32 ]. However, it may affect microRNA binding sites.…”
Section: Discussionmentioning
confidence: 99%